Diagnosis and treatment before assisted reproductive treatments. Guideline of the DGGG, OEGGG and SGGG (S2k Level, AWMF Register Number 015-085, February 2019) - Part 2, Hemostaseology, andrology, genetics and history of malignant disease = Diagnostik und Therapie vor einer assistierten reproduktions-medizinischen Behandlung. Leitlinie der DGGG, OEGGG und SGGG (S2k Level, AWMF-Registernummer 015-085, Februar 2019) - Teil 2, Hämostaseolgie, Andrologie, Humangenetik und Z.n. onkologischen Erkrankungen - Toth, Bettina; Kuon, Ruben-Jeremias; Strowitzki, Thomas; Wischmann, Tewes (Geburtshilfe und Frauenheilkunde, 2019)
Introduction: Supporting and counselling couples with fertility issues prior to starting ART is a multidisciplinary diagnostic and therapeutic challenge. The first German-language interdisciplinary S2k guideline on “Diagnosis and Therapy Before Assisted Reproductive Treatments (ART)” was published in February 2019. The guideline was developed in the context of the guidelines program of the German Society of Gynecology and Obstetrics (DGGG) in cooperation with the Swiss Society of Gynecology and Obstetrics (SGGG) and the Austrian Society of Gynecology and Obstetrics (OEGGG). Aim: In one third of cases, the cause of involuntary childlessness remains unclear, even if the woman or man have numerous possible risk factors. Because the topic is still very much taboo, couples may be socially isolated and often only present quite late to a fertility center. There is no standard treatment concept for these patients at present, as there are currently no standard multidisciplinary procedures for the diagnostic workup and treatment of infertility. The aim of this guideline is to provide physicians with evidence-based recommendations for counselling, diagnosis and treatment. Methods: This S2k guideline was developed on behalf of the Guidelines Commission of the DGGG by representative members from different professional medical organizations and societies using a structured consensus process. Recommendations: This second part of the guideline describes the hematological workup for women as well as additional diagnostic procedures which can be used to investigate couples and which are carried out in cooperation with physicians working in other medical fields such as andrologists, geneticists and oncologists.